Examination of school readiness and factors related to developmental vulnerability in children born very low birth weight. (27th September 2022) - Bando, Nicole; Walton, Kathryn; O'Connor, Deborah L.; Janus, Magdalena; Unger, Sharon L.
Abstract: Background: Many children born very low birth weight (VLBW) experience school struggles with preparedness requiring adequate physical, social, behavioural, cognitive and communication skills. A global assessment of proficiency is necessary to identify those at risk in any such area and direct early intervention accordingly. Study objectives were to characterize developmental vulnerability and school readiness scores in these key domains in a sample of children born VLBW versus their provincial public school system peers and identify early‐life infant and parent factors related to suboptimal school readiness. Methods: The Early Development Instrument teacher assessments of school readiness were collected for a Canadian VLBW sample (NCT02759809). Comparisons between children born VLBW and peers were made. Group differences between children born VLBW considered vulnerable (<10th percentile, not developmentally ready for learning) and not vulnerable were tested and linear regression explored associations between early‐life factors and domain scores. Results: Of 77 available Early Development Instrument assessments, median (interquartile range) assessment age was 6.0 (5.7, 6.2) years, birth weight 950 (793, 1250) grammes and birth gestation 27.4 (25.6, 29.7) weeks. A higher proportion of children born VLBW versus peers exhibited vulnerability in Physical Health and Well‐being (24.7% vs. 16.1%, p  = 0.04), Communication Skills and General Knowledge (23.4% vs. 10.2%, p  = 0.0001) and vulnerability in ≥2 domains (26.0% vs. 14.4%, p  = 0.004). Children born VLBW classified as vulnerable versus not vulnerable had lower birth gestation and 5‐min Apgar. Adjusted regression models found Apgar <7 associated with lower scores for Physical Health and Well‐being (−0.86; 95%CI: −1.71, −0.00; p  = 0.049), Social Competence (−1.77; 95%CI: −2.92, −0.62; p  = 0.003), Emotional Maturity (−1.55; 95%CI: −2.43, −0.66; p  = 0.0009) and Communication Skills and General Knowledge (−1.63; 95%CI: −3.19, −0.06; p  = 0.04). Conclusions: This VLBW sample exhibited poor school readiness in multiple domains. Identification of lower birth gestation and Apgar may assist targeted early interventions to mitigate vulnerability.